A new species of Lepanthes (Pleurothallidinae) from the north of the Central Andes of Colombia - Vieira-Uribe, Sebastián (2022)
A new Lepanthes species from the northern end of the Central Andes of Colombia is described, illustrated, and compared with morphologically similar species. Lepanthes wakemaniae is most similar to L. caesariata but is easily distinguished by its petals with oblong to ovate upper lobes and triangular lower lobes; semi-ovate lip blades, with their inner margins touching above the column; the appendix ligulate and pubescent, and a column with an expanded, orbicular stigma.